Ultrasound prenatal and radiology evaluations in the diagnosis of anencephaly in dog - Case report - da Veiga, Cristiano Chaves Pessoa; de Souza, Bruno Gonçalves; Vieira, Suzana Limeria (Brazilian Journal of Veterinary Medicine, 2013)
ABSTRACT. da Veiga C.C.P., de Souza B.G. &Vieira S.L. [Ultrasound prenatal and radiology evaluations in the diagnosis of anencephaly in dog - Case report]. Avaliações pré-natal ultrassonográfica e radiográfica no diagnóstico de anencefalia em cão - Relato de caso. Revista Brasileira de Medicina Veterinária, 35(2):101-104, 2013. Hospital Veterinário, Instituto de Veterinária, Universidade Federal Rural do Rio de Janeiro, Campus Seropédica, BR 465 km 7, Seropédica, RJ 23897-970, Brasil. E-mail: radiovet@ufrrj.br Anencephaly is a malformation of the head and is among the malformations involving the neural tube defects in the embryo. In humans, the neural tube defects are common birth defects, but in veterinary medicine these malformations are considered rare. Ultrasound examination is widely used in clinical routine as regards pregnancy. Anomalies of the fetus detected by prenatal ultrasound examination have been described in dogs. The objective of this study is to point out the sonographic evaluation the performance of a fetus in the prenatal and radiographic findings, where there was a possibility to diagnose anencephaly. The conclusion of this report was that ultrassonography could be useful in assessing gestational age and the radiographic evaluation allowed identifying anencephaly. In this case, it was demonstrated debilitating disease and studies in embryonic malformations in dogs could be necessary for determining the real importance of these malformations, and whether there are objective factors triggers minor problems with the financial and emotional loss of fetuses.